2011
DOI: 10.4028/www.scientific.net/amr.299-300.139
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Al-Mg-Sc Alloy Processed by Semi-Solid Continuous Casting-Extrusion

Abstract: High tensile strength Al-3Mg-0.5Sc alloy wires can be produced by a method called semi-solid continuous casting-extrusion and on-line solution process (CCES). The effects of artificial aging and the combination of the artificial aging and cold drawing on the microstructures and properties of alloy wires were respectively investigated. TEM observations reveal that a large number of dislocations and Al3Sc particles distributed in the Al-matrix of Al-3Mg-0.5Sc alloy produced by semi-solid CCES.After directly arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As studies of the methods of continuous extrusion of metals have shown [15][16][17][18][19][20][21][22][23][24], their use significantly increases the efficiency of the production of profiles from non-ferrous metals. One of the promising directions in the development of these technologies is the combination of continuous casting with extrusion on a Conform installation with a horizontal carousel mold [21][22][23][24][25][26]. During the operation of the installation, the metal melt is fed through the batcher into the annular groove of the rotating mold wheel and solidifies to contact with the stationary part of the container, formed at the interface of the groove with the arcuate segment (Fig.…”
Section: Introductionmentioning
confidence: 99%